The invisible hands in policy making: A qualitative study of the role of advocacy in priority setting for maternal and child health in Nigeria - Chinyere Okeke; Benjamin Uzochukwu; Maylene Shung-king; Lucy Gilson (Tabriz University of Medical Sciences, 2023)
Background: Maternal and child health is a priority for most governments, especially those in low and middle-income countries (LMICs), due to high mortality rates. The combination of individual and social actions designed to gain political commitment, policy support and social acceptance for health goals are influenced by the interplay between the advocates and the strategies they deploy in planning and advocating for maternal and child health issue. This study aims to deepen our understanding of how advocacy has influenced maternal and child health priority setting in Nigeria. Methods: This is a mixed method study that involved 24 key informant interviews, document review, policy tracking and mapping of advocacy events that contributed to the repositioning of maternal and child health on the political agenda was done. Respondents were deliberately selected according to their roles and positions. Analysis was based on Shiffman and Smith's policy analysis framework of agenda setting. Results: Our findings suggest that use of various strategies for advocacy such as influencers, media, generated different outcomes and the use of a combination of strategies was found to be more effective. The role of advocacy in issue emergence was prominent and the presence of powerful actors, favorable policy window helped achieve desired outcomes. The power of the advocates and the strength of the individuals involved played a key role. Conclusion: This study finds it possible to understand the role of advocacy in policy agenda setting through the application of agenda setting framework. To achieve the health SDG goals, advocacy barriers need to be addressed at multiple levels.